Dynamical properties of a dissipative discontinuous map: A scaling investigation - Aguilar-Sanchez, R.; Leonel, Edson D. [UNESP]; Mendez-Bermudez, J. A. (Elsevier B.V., 2013)
The effects of dissipation on the scaling properties of nonlinear discontinuous maps are investigated by analyzing the behavior of the average squared action < I-2 > as a function of the n-th iteration of the map as well as the parameters K and gamma, controlling nonlinearity and dissipation, respectively. We concentrate our efforts to study the case where the nonlinearity is large; i.e., K >> 1. In this regime and for large initial action I-0 >> K, we prove that dissipation produces an exponential decay for the average action < I >. Also, for I-0 congruent to 0, we describe the behavior of < I-2 > using a scaling function and analytically obtain critical exponents which are used to overlap different curves of < I-2 > onto a universal plot. We complete our study with the analysis of the scaling properties of the deviation around the average action omega. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Scaling; Discontinuous map; Dissipation